Identification, morphology of Citrus L. (Aurantioideae-Rutaceae Juss.) and its traditional uses in Riau Province, Indonesia (Biodiversitas Journal of Biological Diversity, 2022)
Abstract. Sofiyanti N, Iriani D, Wahyuni PI, Idani N, Lestari P. 2022. Identification, morphology of Citrus L. (Aurantioideae-Rutaceae Juss.) and its traditional uses in Riau Province, Indonesia. Biodiversitas 23: 1038-1047. The genus Citrus (Rutaceae) is an important fruit crop in the world. The species of Citrus are extensively cultivated for fresh fruit and processed juice market. In addition, Citrus members have a great ability to cross and produce intra or intergeneric hybrids. Therefore, the taxonomic identification of the cultivars has been a serious challenge for botanists and agronomists. In Riau Province (Indonesia), the cultivars of this genus are grown for various uses. The aims of this study are to identify Citrus taxa in Riau Province, examine their morphological characters, and document their uses by local people. Samples were collected in the field. The result shows a total of 18 Citrus members were identified in this study. The Citrus morphologies vary among the members. Each Citrus identified in this study shows its morphological characteristic of vegetative and generative parts. Numerous local uses of Citrus are recorded in this study, e.g. fresh consumed, traditional drink, folklore, herb, spice and ornamental. The parts of Citrus used are whole plant, leaf, pericarp and pulp. The uses of Citrus recorded in this study are for herb and spice, dessert, traditional drink and treatment, folklore, and ornamental plant. This study provides the first record of the morphological characteristic of Citrus in this province and the uses of its members.